Assessment of farmer exposure to pesticides applied in paddy fields using mathematical modelling - Nurin Dalila Mohd Shobri (2020)
This study investigates how field practices in handling and applying pesticides may influence the patterns of paddy farmers' exposure to pesticides applied in the fields. Exposure of eleven selected paddy farmers was estimated based on the latest European operator exposure model, namely Agricultural Operator Exposure Model and then assessed against the Acceptable Operator Exposure Level (AOEL) for individual pesticide active substances. Overall, the total number of active substances handled by the eleven selected farmers ranged from 2 to 11 compounds across a whole cropping season (March — June 2019). Of eleven farmers, only one farmer had one application with estimated exposure to dimethoate greater than AOEL (1.85 x 10-3 mg kg bw-1 day-1). This study found that the exceedance of AOEL was mainly influenced by the use of powder formulations during mixing/loading that contributed to more approximately 22% of total pesticide exposure across the whole cropping seasons.